Simultaneous Policy Expansion and Reduction? Tracing Dismantling in the Context of Experimentalist Governance in European Union Environmental Policy. (1st December 2021) - Pollex, Jan
Abstract: Research on EU policy has detected two developments that seem contradictory at first sight. On the one hand, there is evidence of continued rule growth and policy expansion. On the other hand, research points to dismantling, primarily via the backdoor and in comitology. This article investigates how experimentalist governance settings can provide opportunities for policy reduction within an overall expanding policy. Therefore, it focuses on the EU's Ecodesign policy which is characterized by a mix of binding and voluntary measures that qualify as experimentation. Although the voluntary measures contribute to rule growth, they are characterized by lenient standards compared to binding regulation under Ecodesign. In particular, they allow the Commission to follow a strategy of non‐adjustment. The article points to simultaneous expansion and dismantling processes not yet fully covered in previous research. Experimentalist governance poses a crucial element in enabling such developments leading to shallow expansion and allowing for dismantling.